La separación de los padres y el rendimiento escolar de los niños de 5 a 6 años del centro San Juan Bosco de la ciudad de Loja - Cobos Sanmartín, Liliana Mireya (2015)
These projects it’s about parental separation and children’s academic performance from 5 to 6 years whostudyin “SanJuanBoscoCenter”ofLojacity during. in this way this project contemplate the general objective to determine how parental separation influencesin children’s academic performance from 5 to 6 years whostudyin “SanJuanBoscoCenter”ofLoja city, therefor, this project has been undertaken in order to determine how parental separation affects the educational performance of children from 5 to 6 years whostudyin “SanJuanBoscoCenter”ofLojacity. The main research methods used in this project were: • Scientist method, which constituted a systematic process based on observation and analysis, based on the synthesis , impartiality and objectivity of facts; • Hypothetical deductive method , that since the formulation of the project made possible transform abstract points to definite, which means, transform general ideas, prioritizing and organizing concrete issues to reach the research problem, likewise, this method was used to specify the assumptions, variables, indicators and research instruments from the theorical framework. • Inductive methodthat helpedto examine the objectand through the useofresearch tools,allowed us to meetitsempirical particularities then, by searchingrelations givenbetween them,integrate them,describing and seeking its characteristics andcausal explanations, which information was groupedintables and charts and after that this information was described, analyzedand interpreted. Onceordered, processed and analyzed this information waspossible to concludethat the parental separation ineffectaffectschildren’s academic performance from 5 to 6 years whostudyin “SanJuanBoscoCenter”ofLoja city. After the conclusions, we givesome recommendationsfor the authoritiesofSanJuanBoscoCenter, professors andparents in order to take action to facethe problem.